Outgrower Schemes - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance on the design and implementation of outgrower schemes to achieve mutually beneficial outcomes for investors and smallholders. Outgrower schemes have gained prominence as a business model that can benefit both smallholders and investors. Such schemes can improve smallholders’ access to markets, finance, infrastructure, and improved growing techniques; can enhance investors’ access to land, labor, and quality produce; and can improve investor-community relations. Associated risks include overdependency, exploitation of power differences, entrenchment of inequalities, lower-than-expected production, and side-selling. Achieving the potential benefits and minimizing the associated risks requires careful design and implementation.